2013
DOI: 10.2215/cjn.03280313
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Frequent Hemodialysis on Ventricular Volumes and Left Ventricular Remodeling

Abstract: SummaryBackground and objectives Higher left ventricular volume is associated with death in patients with ESRD. This work investigated the effects of frequent hemodialysis on ventricular volumes and left ventricular remodeling.Design, setting, participants, & measurements The Frequent Hemodialysis Network daily trial randomized 245 patients to 12 months of six times per week versus three times per week in-center hemodialysis; the Frequent Hemodialysis Network nocturnal trial randomized 87 patients to 12 months… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
59
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(64 citation statements)
references
References 32 publications
(34 reference statements)
2
59
0
3
Order By: Relevance
“…Conventional approaches to achieve this have largely relied on the control of pressure and volume overload. Daily dialysis is an effective approach in this respect, and the Frequent Hemodialysis Network trials reported that HD six times weekly led to an adjusted mean reduction in LV mass (213.8 g; 95% CI, 221.8 to 25.8g) and LV enddiastolic volume (211.0%; 95% CI, 216% to 26%), with no change in EF over 12 months compared with conventional thrice-weekly HD (34,35). This trial reports a similar reduction in LV mass (215.6 g; 95% CI, 229.4 to 21.9 g) and LV end-diastolic volume (223.8 ml; 95% CI, 244.7 to 22.9 ml), with no change in EF over 12 months.…”
Section: Discussionmentioning
confidence: 99%
“…Conventional approaches to achieve this have largely relied on the control of pressure and volume overload. Daily dialysis is an effective approach in this respect, and the Frequent Hemodialysis Network trials reported that HD six times weekly led to an adjusted mean reduction in LV mass (213.8 g; 95% CI, 221.8 to 25.8g) and LV enddiastolic volume (211.0%; 95% CI, 216% to 26%), with no change in EF over 12 months compared with conventional thrice-weekly HD (34,35). This trial reports a similar reduction in LV mass (215.6 g; 95% CI, 229.4 to 21.9 g) and LV end-diastolic volume (223.8 ml; 95% CI, 244.7 to 22.9 ml), with no change in EF over 12 months.…”
Section: Discussionmentioning
confidence: 99%
“…The strong correlation between LV mass and LVEDV in ESRD reflects the fact that LV hypertrophy is an adaptive response, at least in part, to chronic volume overload. In this issue of CJASN, this relationship between LV mass and LVEDV was reflected in the finding that most participants receiving frequent dialysis had reductions in both LV mass and LVEDV ( Figure 4 in Chan and colleagues' article) (7).…”
mentioning
confidence: 93%
“…With frequent dialysis, there was a proportional decrease in both stroke volume (change, 210.58%) and LVEDV (change, 211.19%) ( Table 2 in Chan and colleagues' article) (7). Although this means that LV ejection fraction (stroke volume/LVEDV) did not change, we may infer that stroke work (stroke volume3LV Table 2 in Chan and colleagues' article).…”
mentioning
confidence: 95%
See 2 more Smart Citations